Size and Morphology Investigation of PZT Nanofibers for Energy Harvesting Applications using Digital Holography - Plaipichit, S.; Wicharn, S.; Puttharugsa, C.; Bintachitt, P.; Aeimbhu, A.; Buranasiri, P. (My University, 2025)
Polyvinylidene fluoride fibers composed of piezoelectric lead zirconate titanate under different fabrication conditions were investigated using digital holography technique. Larger PZT content and larger feed rates results in larger diameters, and thicker fibers respectively.